Lith. vedą̃ = Sl. *vedǫtь̍: the accentuation of the nom. pl. of active participles as further proof of finite origin - Majer, Marek (Baltistica, 2017)
The aberrant form of the nom. pl. of Balt. active participles (Lith. vedą̃ etc.) has been aptly explained (Cowgill, partly anticipated by Endzelīns) as the intrusion of the old finite 3. pl. (< PIE *wedʰonti etc.) into the nominal paradigm of the participle. However, it has been unnoticed so far that the accentuation of the form – synchronically completely isolated and unexpected, as the only end-stressed athematic nom. pl. – is also explained by, and therefore corroborates, this theory. The accent corresponds exactly to the PBSl. reconstruction 3. pl. pres. *wedantı̍ (conceivably, although less plausibly, PBSl. *weda̍nti) pointed to by Proto-Slavic *vedǫtь̍.